Preoperative portal vein or portal and hepatic vein embolization: DRAGON collaborative group analysis. Issue 7 (1st March 2021) - Heil, J; Korenblik, R; Heid, F; Bechstein, W O; Bemelmans, M; Binkert, C; Björnsson, B; Breitenstein, S; Detry, O; Dili, A; Dondelinger, R F; Gerard, L; et al.
Abstract: Background: The extent of liver resection for tumours is limited by the expected functional reserve of the future liver remnant (FRL), so hypertrophy may be induced by portal vein embolization (PVE), taking 6 weeks or longer for growth. This study assessed the hypothesis that simultaneous embolization of portal and hepatic veins (PVE/HVE) accelerates hypertrophy and improves resectability. Methods: All centres of the international DRAGON trials study collaborative were asked to provide data on patients who had PVE/HVE or PVE on 2016–2019 (more than 5 PVE/HVE procedures was a requirement). Liver volumetry was performed using OsiriX MD software. Multivariable analysis was performed for the endpoints of resectability rate, FLR hypertrophy and major complications using receiver operating characteristic (ROC) statistics, regression, and Kaplan–Meier analysis. Results: In total, 39 patients had undergone PVE/HVE and 160 had PVE alone. The PVE/HVE group had better hypertrophy than the PVE group (59 versus 48 per cent respectively; P  = 0.020) and resectability (90 versus 68 per cent; P  = 0.007). Major complications (26 versus 34 per cent; P  = 0.550) and 90-day mortality (3 versus 16 per cent respectively, P = 0.065) were comparable. Multivariable analysis confirmed that these effects were independent of confounders. Conclusion: PVE/HVE achieved better FLR hypertrophy and resectability than PVE in this collaborative experience. Abstract : The aim of this international multicentre retrospective cohort study from the DRAGON collaborative was to compare simultaneous portal vein and hepatic vein embolization (PVE–HVE) with contemporaneously performed PVE at participating centres to evaluate safety, feasibility, and efficacy.